Incorporating assessment in a pattern-based design process for CSCL scripts. - Villasclaras-Fernández, Eloy D.; Hernández-Leo, Davinia; Asensio-Pérez, Juan I.; Dimitriadis, Yannis (Computers in Human Behavior, 2009)
Scripting has already been shown to be a way of increasing the chances of effective collaborative learning, and especially when computer support is available. Formal specifications, such as IMS-LD, and software authoring tools have provided instructional designers and educational practitioners with mechanisms for the creation and automation of flexible collaborative learning scripts ready to run in real scenarios. Within the context of Computer Supported Collaborative Learning (CSCL) script design, the application of design patterns has been proposed as the basis for a design process that promotes the reuse of good practices, implemented in an IMS-LD authoring tool, Collage. However, it is well known that assessment is a key aspect in real learning scenarios, and therefore it should be included in CSCL scripts. In this sense, this paper reports data and findings derived from two case studies performed to explore how assessment design can be included in the aforementioned pattern-based process. Results provide preliminary evidence that additional support is necessary for assessment design within this process for non-expert users. In order to tackle this limitation, the use of assessment patterns is analyzed. Evidence gathered in the case studies supports the need, adequacy and feasibility of a more systematic assessment-aware design process for CSCL scripts. Copyright (c) 2009 Elsevier Ltd.